2014
DOI: 10.1177/2167702614553789
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Cognitive Vulnerabilities to Depression and Anxiety

Abstract: Cognitive theories of psychopathology posit that maladaptive patterns of cognitions confer elevated risks to individuals in the development of psychological disorders. This meta-analysis examined the extent to which six cognitive vulnerabilities associated with depression (i.e., pessimistic inferential style, dysfunctional attitudes, and ruminative style) and anxiety (i.e., anxiety sensitivity, intolerance of uncertainty, and fear of negative evaluation) were related with one another. A total of 159 effect siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
88
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 174 publications
(160 reference statements)
9
88
1
4
Order By: Relevance
“…Hong and Cheung (2015) suggested that several cognitive vulnerabilities may share a common core of IU and, therein, fearing the unknown. Indeed, IU mediates the relationship between neuroticism and WHAT UNCERTAINTIES REMAIN?…”
Section: What Is Known?mentioning
confidence: 99%
See 4 more Smart Citations
“…Hong and Cheung (2015) suggested that several cognitive vulnerabilities may share a common core of IU and, therein, fearing the unknown. Indeed, IU mediates the relationship between neuroticism and WHAT UNCERTAINTIES REMAIN?…”
Section: What Is Known?mentioning
confidence: 99%
“…Models of psychopathology posit that uncertainty is a central feature in anxiety-related experience (Carleton, 2016) and the incapacity to endure unknowns appears to be a robust vulnerability factor associated with a range of psychological disorders (Grupe & Nitschke, 2013;Hong & Cheung, 2015). IU was originally defined as a broad construct that reflects "cognitive, emotional, and behavioral reactions to uncertainty in everyday life situations" (Freeston, Rhéaume, Letarte, Dugas, & Ladouceur, 1994, p. 792).…”
Section: What Is Known?mentioning
confidence: 99%
See 3 more Smart Citations